Social Stereotypes with Regard to Older People: Experience of European Social Survey Methodology Use in Ukraine - Grishina, Tatiana (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
Social stereotypes toward elderly are analyzed in this paper. They are using for justification of existing social inequality. Author examined peculiarities of Model of Stereotype Content (MSC) developed by A. Cuddy and S. Fiske. It takes into account the diversity of social stereotypes that may be both onedimensional and multi-dimensional, because they contain negative and positive beliefs. This model proposes potentially universal principles of societal stereotypes and their relation to social structure. For stereotype’s measuring are used two indicators: warmth and competence. These indicators relate to the social status and competitiveness. In this paper are presented the results of construction of a Model of Stereotype Content for Ukraine.